Dyserythropoiesis and ineffective erythropoiesis in Plasmodium vivax malaria. - Wickramasinghe, SN; Looareesuwan, S; Nagachinta, B; White, N (1989)
Nine Thai adults with P. vivax malaria were investigated. Light and electron microscope studies of marrow aspirates revealed morphological evidence of dyserythropoiesis in six of them. Dyserythropoiesis was most marked in the four most anaemic patients. In these four patients the electron microscope also revealed the presence of erythroblasts at various stages of degradation within the cytoplasm of macrophages. Neither the dyserythropoiesis nor the ineffective erythropoiesis could be attributed to a deficiency of vitamin B12, folate or iron. The abnormalities of erythropoiesis seemed to result from the P. vivax infection itself. Other bone marrow reactions seen in this infection included macrophage hyperplasia, plasmacytosis and increased eosinophil granulocytopoiesis. Unlike in severe P. falciparum malaria, the microvasculature of the marrow was not obstructed by parasitized red cells.